PROJECT CITIZEN: DEVELOPMENT OF SOCIAL SKILLS AND UNDERSTANDING OF CONTEMPORARY ISSUES (STUDY AT AHMAD DAHLAN UNIVERSITY) - Nufikha Ulfah; Yayuk Hidayah; Mirza Hardian; Meiwatizal Trihastuti (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:In a cluster of social science, Citizenship Education has a role in developing social skills and become a media of preparing smart and thoughtful citizen towards citizenship issues, and it also gives alternative solution for a particular problem. This study aimed to describe the students’ social skills and contemporary issue understanding through Project Citizen-Based Learning in Citizenship Education as a part of General Compulsory Courses (MKWU). This research used descriptive qualitative method which took place at Ahmad Dahlan University. This research indicated that the steps of Project Citizen could develop the students’ social skills and contemporary issue understanding. The development of social learning through Citizen Project-based learning model in Citizenship Education as MKWU was carried out through cooperation, mutual assistance, communication, and responsibility. The understanding of contemporary issues was carried out through the principles of Project Citizen which included; (1) possession of soft-skill communication in doing task/project, (2) ability to manage time for completing task/project, and (3) interaction with technology in completing project.Abstrak:Dalam rumpun ilmu sosial, Pendidikan Kewarganegaraan memiliki peran dalam mengembangkan keterampilan sosial, dan menjadi wahana dalam mepersiapkan warga negara yang cerdas dan peka terhadap isu-isu Kewarganegaran serta mampu memberikan solusi alternatif terhadap suatu permasalahan. Penelitian ini bertujuan untuk pengembangan keterampilan sosial dan pemahaman isu kekinian mahasiswa melalui model pembelajaran berbasis Project Citizen pada MKWU Pendidikan Kewarganegaraan. Penelitian ini menggunakan metode kualitatif deskriptif yang berlokasi di Universitas Ahmad Dahlan Yogyakarta. Hasil penelitian menunjukan bahwa langkah-langakah Project Citizen dapat mengembangkan keterampilan sosial dan pemahaman isu kekinian mahasiswa. Pengembangan keterampilan sosial melalui model pembelajaran berbasis Project Citizen pada MKWU Pendidikan Kewarganegaraan meliputi kerjasama, gotong royong, berkomunikasi dan bertanggung jawab. Sementara itu, pemahaman terhadap isu kekinian dilakukan melalui prinsip Project Citizen yang meliputi (1) kepemilikan soft-skill berkomunikasi saat mengerjakan tugas, (2) kemamuan mengatur waktu dalam menyelesaikan tugas, dan (3) interaksi dengan teknologi dalam penyelesian tugas.